1, 3‐Diynes: A Versatile Precursor in Transition‐Metal Catalyzed (Mediated) C−H Functionalizations. Issue 3 (13th December 2022) - Kumar, Sanjeev; Kumar Sabbi, Tharun; Pingale, Rasika; Girase, Pradeep; Kanchupalli, Vinaykumar
Abstract: Transition metal‐catalyzed C−H functionalization of diverse arenes with alkyne units has attracted enormous attention for decades since they provide straightforward access to various functionalization/annulations, which are commonly present in bioactive compounds and natural products. Recently, conjugated alkynes (1, 3‐diynes) have been utilized as key coupling partner in many C−H activation reactions due to their versatile characteristic properties. The presence of two C≡C bonds in conjugated 1, 3‐diyne brings the new diversity in synthetic transformations, such as chemo‐, regioselective pathways, mono‐bis functionalizations, cascade annulations, etc. Herein, we summarized the latest developments in the realm of transition‐metal‐catalyzed C−H functionalizations of diverse arenes with 1, 3‐diynes. Moreover, we highlighted the diverse transformations, conditions, mechanisms and applications of the corresponding reaction in detail. Abstract : Transition metal‐catalyzed C−H functionalizations with alkynes have become very familiar in organic synthesis. However, the alkyne surrogate, such as 1, 3‐diynes in the C−H activation field is still in the early stage. This review summarizes the recent advances of transition metal‐catalyzed direct C−H annulation/alkenylation of arenes with 1, 3‐diyne precursors and their notable applications in organic synthesis.